Application Of Singing Methods To Improve Vocabulary Mastery In Learning Arabic Language At Madrasah Ibtida’iyah - Hanum, Amiroh Nubaila (Universitas Muhammadiyah Sumatera Barat, 2023)
This research aims to improve the quality of children's memorization in acquiring Arabic vocabulary using singing techniques. Basically, in all circles, children are happy and interested when invited to listen to and sing songs. They will find it easier when they are invited to memorize and understand the Arabic vocabulary contained in the songs they sing. Therefore, in general music is an important and influential thing in the teaching and learning process for students. The results show that early age students enjoy learning Arabic with singing techniques. Because this really helps students remember the vocabulary taught by the teacher. So, it can be concluded that singing techniques can improve students' mastery of Arabic vocabulary from an early age, especially Madrasah Ibtida’iyah students.